2015
DOI: 10.1080/13607863.2015.1075959
|View full text |Cite
|
Sign up to set email alerts
|

CODEMamb– an observational communication behavior assessment tool for use in ambulatory dementia care

Abstract: In summary, CODEM is a reliable and valid instrument that can be used to collect important information with the ultimate aim of supporting communication with people with dementia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 37 publications
2
26
0
Order By: Relevance
“…In addition, people with dementia may not always realize that they need care or treatment (87). However, at least in the early and intermediate stages of the condition, these sort of problems could be avoided or mitigated through communication strategies and mechanisms directed to reminding the person of things they may not recall, or explaining treatment information in simpler terms or by rectifying misunderstandings, or planning conversations with the person in moments in which they are sharper (78,(88)(89)(90). Unfortunately, the majority of national legislations do not provide mechanisms to assist a person in overcoming the obstacles created by their condition, and rules that require active help before declaring a person incapable (91).…”
Section: Legal Capacity Healthcare Decisions and Dementiamentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, people with dementia may not always realize that they need care or treatment (87). However, at least in the early and intermediate stages of the condition, these sort of problems could be avoided or mitigated through communication strategies and mechanisms directed to reminding the person of things they may not recall, or explaining treatment information in simpler terms or by rectifying misunderstandings, or planning conversations with the person in moments in which they are sharper (78,(88)(89)(90). Unfortunately, the majority of national legislations do not provide mechanisms to assist a person in overcoming the obstacles created by their condition, and rules that require active help before declaring a person incapable (91).…”
Section: Legal Capacity Healthcare Decisions and Dementiamentioning
confidence: 99%
“…Studies and pilot projects on treatment and care decision-making for people with dementia show how it is possible to organize support around the person without the need of a mental capacity assessment. A team of German researchers has developed the CODEMamb tool, which allows for investigating the needs for (conversational) support and adjustments of a person with dementia by observing their communication behavior and resources ( 89 ). In a Norwegian pilot study investigating shared healthcare decision-making involving people with dementia, Smebye, Kirkevold, and Engedal identified different levels of support needed, which present with the development of a person's impairment, but in a fluid way, just adapting to the person's conditions and reactions.…”
Section: The Crpd Dementia and Healthcare Decisionsmentioning
confidence: 99%
“…The Unites States has seen a plethora of research in the past 20 years on improving assessment of pain in people with dementia (Dening, 2014;Hadjistavropoulos, Herr, Prkachin, Craig, Gibson, Lukas, & Smith, 2014;Lichtner et al, 2014;McIlfatrick, 2015;Zwakhalen, Hof, & Hamers, 2012). Multiple assessment tools have been developed that assess behavioral symptoms of pain in people with dementia (Ali et al, 2015;Ersek, Herr, Neradilek, Buck, & Black, 2010;James, 2011;Knebel, Haberstroh, Kümmel, Pantel, Schröder, 2015). Kovach et al (2012) have consistently found that improving nurse's assessment of behavioral symptoms leads to decreased pain and agitation in PWD Kovach et al, 2010;Kovach et al, 2012).…”
Section: The Role Of Assessmentmentioning
confidence: 99%
“…ever, efforts to use a resource-oriented approach to support and treat PwD exist [2][3][4][5]. This approach attempts to identify the deficits and resources of PwD and to focus on remaining abilities in order to enhance their communication and decision-making abilities.…”
Section: Introductionmentioning
confidence: 99%